2022
DOI: 10.1038/s41598-022-16163-w
|View full text |Cite
|
Sign up to set email alerts
|

Sex disparities in mortality among patients with kidney failure receiving dialysis

Abstract: Females are known to have a better survival rate than males in the general population, but previous studies have shown that this superior survival is diminished in patients on dialysis. This study aimed to investigate the risk of mortality in relation to sex among Korean patients undergoing hemodialysis (HD) or peritoneal dialysis (PD). A total of 4994 patients with kidney failure who were receiving dialysis were included for a prospective nationwide cohort study. Cox multivariate proportional hazard models we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“… 43 Another study that included only Korean patients with kidney failure on dialysis reported that the survival advantage in women as seen in the general population was maintained but did not find any difference in cardiovascular‐related death between men and women. 44 It is well known that among people with ESKD requiring maintenance dialysis, women lose the survival advantage over men, as seen in the general population, possibly related to cardiovascular risk, hormonal factors, differences in vascular access, comorbidities, anemia management, and socioeconomic factors. 45 In the general population, menopause (and particularly early menopause) is associated with an increased incidence of cardiovascular disease and mortality.…”
Section: Discussionmentioning
confidence: 99%
“… 43 Another study that included only Korean patients with kidney failure on dialysis reported that the survival advantage in women as seen in the general population was maintained but did not find any difference in cardiovascular‐related death between men and women. 44 It is well known that among people with ESKD requiring maintenance dialysis, women lose the survival advantage over men, as seen in the general population, possibly related to cardiovascular risk, hormonal factors, differences in vascular access, comorbidities, anemia management, and socioeconomic factors. 45 In the general population, menopause (and particularly early menopause) is associated with an increased incidence of cardiovascular disease and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic factors associated with the female gender that cause this decrease in survival remain controversial. A less protective effect of body mass index (BMI) on HD mortality, associated with a different rate of skeletal muscle and fat due to sex hormones, is one of the most recent hypotheses [25]. However, the effect of diabetes is the most reported interaction factor on the different survival rates observed between sexes in all causes of death [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of data from the Asian population and no data from India regarding the sex disparity in practice patterns of hemodialysis patients. Only one study from Korea showed that women had better survival than men on dialysis due to a lower risk of non-infection and non-cardiovascular related mortality ( 5 ). We aimed to evaluate distinctions in hemodialysis-related attributes between sexes in two state government-run hemodialysis centers in South India.…”
Section: Introductionmentioning
confidence: 99%